Differences among Costa Rican public and private tertiary education: returns and overeducation - Blanco, Laura Cristina (2020)
Overeducation rates were estimated for the Costa Rican graduate working population using the National Household Survey 2011-2017. Further on, Mincerian wage equations were estimated using ordinary least squares to analyze the existing relationship between wages and the type of university attended, degree subject, area and skill mismatches. Results show that attending a public university is associated with a wage premium ranging from 4.7% to 9.5%. This premium varies by degree subject, but public universities exhibit an advantage in most cases. For elderly cohorts, the premium associated with being a graduate from a public university disappears. Genuine overeducation is not found to be a problem in the Costa Rican labor market, despite the existence of a considerable percentage of apparently overeducated graduates; and this percentage is found to be higher among public universities alumni.